Efektifitas pemberian jahe, susu kedelai (soya) dan madu (jesoma) terhadap penurunan nyeri dismenore pada remaja putri - Rofiasari, Linda; Lubis, Tika; Sare, Dewi Nurlaela; Gardenia, Meli Sandra (Poltekkes Kemenkes Aceh, 2024)
Background: Dysmenorrhea is discomfort that can occur when experiencing menstruation which can have an impact on disrupting physical activities.Objectives: The focus of this research is to determine the effect of ginger, soy milk and honey (Jesoma) on reducing dysmenorrhea pain complaints.Methods: The research method used was Quasi-experimental with a one group pre-post test design approach. Sampling in this study used a purposive sampling technique with the sampling criteria being ready to be respondents, female students who were still active and experiencing dysmenorrhea and not experiencing secondary dysmenorrhea. The number of samples in this research was 32 female students at SMK 1 Ketapang. The pre-test in this research was carried out before the treatment and the post-test was carried out after the research by giving ginger, soy milk and honey (Jesoma).Result : Data analysis used the Wilcoxon test with an error rate of <0,05. The statistical results obtained a p-value of 0,000, so there was an effect of giving ginger, soy milk and honey (Jesoma) on reducing dysmenorrhea pain. Conclusion: In order to obtain the best intervention method in reducing dysmenorrhea, researchers can then carry out laboratory tests to determine the content of ginger, soy milk and honey (Jesoma) and combine it with several methods to obtain the best method in reducing dysmenorrhea.